The short term feasibility of abdominoperineal resection with prostatectomy for locally advanced rectal cancer: open and laparoscopic cases report - Nakanishi, Ryota (Int Cancer Conf J, 2015)
Total pelvic exenteration is often selected for advanced rectal cancer with prostatic invasion. The aim of this study was to evaluate the short term feasibility of the abdominoperineal resection with prostatectomy for locally advanced rectal cancer. We performed abdominoperineal resection with prostatectomy for 3 patients with locally advanced rectal cancer, including 2 patients by totally laparoscopic procedure. Patients’ background, intra- and postoperative factors and short-term prognosis were evaluated. All patients underwent complete resection of primary tumor with negative surgical margins. We could perform the surgery by both open and laparoscopic procedure in collaboration with urologist. There was no operation related mortality. One patient who was treated by open procedure had urinary anastomotic leakage. No patient had recurrenced, but one patient died of other disease. Our experience suggests that open or laparoscopic abdominoperineal resection with prostatectomy could be an alternative to total pelvic exenteration for the patients with rectal cancer invading the prostate. The collaboration with the urologist would be important to perform quality-controlled surgery.